CLINICAL CHARACTERISTICS OF MINORS PATIENTS OF FEMALE PSYCHIATRIC DEPARTMENT № 6 OF “SPECIALIZED NEUROPSYCHIATRIC HOSPITAL” OF THE MINISTRY OF HEALTH OF THE KRASNODAR REGION - E. V. Darin (Медицинский вестник Юга России, 2020)
The aim of the work is to describe the structure of the psychopathology of minor patients treated in a hospital. Inpatient medical records of 39 minor patients who were admitted for treatment in 2018 to the women’s general psychiatric department No. 6 of the «Specialized Psychoneurological Hospital of the Ministry of Health» of the Krasnodar Territory were examined. The data obtained as a result of the study on the nosological affiliation of the inpatient population of adolescent patients, epidemiological, clinical and social factors can be useful for further comparative studies with subsequent scientific substantiation of proposals to optimize the organization of the provision of psychiatric inpatient care for children and adolescents in order to improve its quality.